Pengaruh Stres Kerja dan Kepuasan Kerja Terhadap Perilaku Cyberloafing Karyawan Studi Kasus Lembaga Manajemen Infaq Kantor Pusat - Moh. Isra Benasmi; Muhammad Ridwan Basalamah; Aleria Irma Hatneny (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The internet is a big leap that has occurred in the industrial,technology, information and communication sectors that move dynamically which can be processed to provide faster and more useful information. The internet has been used in various fields, one of which is the world of work, the use of the internet whose initial function is to speed up and simplify an employee's performance also has a negative impact which gives free access to the world of social media. In the world of work, the phenomenon of internet use that has nothing to do with work becomes the focus of a problem called Cyberloafing. The purpose of this study was to determine the effect of job stress and job satisfaction on the cyberloafing behavior of employees at the Surabaya Headquarters Infaq Management Institute.This research method uses a quantitative approach, namely the process of finding knowledge using numbers as a tool to analyze information about what you want to know, the results of this study are that the work stress variable does not have a significant influence on cyberloafing behavior with a significant value of 0.557 while the job satisfaction variable has a significant effect. significant to cyberloafing behavior with a significant value of 0.031. Keywords: Job stress, Job Satisfaction, Cyberloafing, Internet